2019
DOI: 10.1111/nph.16065
|View full text |Cite
|
Sign up to set email alerts
|

Lateral root initiation requires the sequential induction of transcription factors LBD16 and PUCHI in Arabidopsis thaliana

Abstract: Summary Lateral root (LR) formation in Arabidopsis thaliana is initiated by asymmetric division of founder cells, followed by coordinated cell proliferation and differentiation for patterning new primordia. The sequential developmental processes of LR formation are triggered by a localized auxin response. LATERAL ORGAN BOUNDARIES‐DOMAIN 16 (LBD16), an auxin‐inducible transcription factor, is one of the key regulators linking auxin response in LR founder cells to LR initiation. We identified key genes for LR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…LBD proteins orchestrate a lot of plant developmental processes and respond to environmental stimuli, especially play the essential roles in the regulation of lateral organ development and metabolic processes. Several LBD genes, such as LBD16, LBD13, LBD18, and LBD29 have been proven to play important roles in regulating lateral root development in Arabidopsis (Cannon et al 2004;Goh et al 2019;Cho et al 2019;Lee et al 2019a). LBD18 controls lateral root development via inhibition of LBD18 DNAbinding activity (Lee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LBD proteins orchestrate a lot of plant developmental processes and respond to environmental stimuli, especially play the essential roles in the regulation of lateral organ development and metabolic processes. Several LBD genes, such as LBD16, LBD13, LBD18, and LBD29 have been proven to play important roles in regulating lateral root development in Arabidopsis (Cannon et al 2004;Goh et al 2019;Cho et al 2019;Lee et al 2019a). LBD18 controls lateral root development via inhibition of LBD18 DNAbinding activity (Lee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have confirmed that LBD proteins play an essential role in the regulation of the growth and development of a variety of plants. AthLBDs are found to be involved in various tissues development such as leaf development (Semiarti et al 2001) and lateral root initiation (Goh et al 2019;Cho et al 2019;Lee et al 2019a), as well as signaling transduction such as cytokinin (Naito et al 2007) and gibberellin pathways (Zentella et al 2007). To be specific, AthLBD16 is involved in instigating the migration of nuclei and in the asymmetric division of lateral root founder cells to promote lateral root initiation (Goh et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis , AtLBD16 , AtLBD17 , AtLBD18 and AtLBD29 were reported as important regulators of callus initiation in different organs, and they regulate lateral root formation [ 90 ]. Additionally, LBD16 was reported to be responsible for the initiation of lateral roots and for determining the asymmetry in the founder cells of lateral roots prior to cell division [ 95 , 96 ]. In this study, LBD16 was predicted as the target of miR837-3p, and its expression was found to be significantly down-regulated, while those of miR837-3p showed significant up-regulation upon RA-inoculation, suggesting that the RA-mediated regulation of the miR837-3p-LBD16 module may be involved in lateral root formation in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, initiation of LR formation starts from the founder cells' asymmetric division, and through subsequent cell proliferation and differentiation to form new primordia. AtLBD16 is a key member for LR formation in an auxin-dependent manner [11,102]. LR initiation requires the sequential induction of transcription factor gene AtLBD16 and its target PUCHI [102].…”
Section: Functions Of Lbd Proteins In Class Ib Cladementioning
confidence: 99%
“…AtLBD16 is a key member for LR formation in an auxin-dependent manner [11,102]. LR initiation requires the sequential induction of transcription factor gene AtLBD16 and its target PUCHI [102]. AtLBD18 and ARFs form a double positive feedback loop, as AtLBD18 can not only bind to the ARF19 promoter directly but also interacts with ARF7 and ARF19 [101].…”
Section: Functions Of Lbd Proteins In Class Ib Cladementioning
confidence: 99%